Stabilization and Controller Design of 2D Discrete Switched Systems with State Delays under Asynchronous Switching - Shipei Huang; Zhengrong Xiang; Hamid Reza Karimi (Abstract and Applied Analysis)
This paper is concerned with the problem of robust stabilization for a class of uncertain two-dimensional (2D) discrete switched systems with state delays under asynchronous switching. The asynchronous switching here means that the switching instants of the controller experience delays with respect to those of the system. The parameter uncertainties are assumed to be norm-bounded. A state feedback controller is proposed to guarantee the exponential stability. The dwell time approach is utilized for the stability analysis and controller design. A numerical example is given to illustrate the effectiveness of the proposed method.